MODEL BANK TANAH PERTANIAN UNTUK MEWUJUDKAN INDONESIA BERDAULAT PANGAN - Wahyu Benny Mukti Setiyawan; Nabila Chyntia Dahani (Qistie Jurnal Ilmu Hukum, 2020)
This study is a normative study, using statute approach and concept approach. The results of the study are the agricultural land banking model is the right concept to be applied in order to carry out land acquisition for agricultural land. The concept has previously been widely applied in various countries, namely the United States, Switzerland, and the Netherlands. Implementation of the concept of agricultural land banks in these countries proved successful. It is also necessary to apply the concept of agricultural land banking in Indonesia from the planning stage to the comprehensive control stage so that in the future there will be no significant problems in the realization of food sovereignty in Indonesia in terms of agriculture, especially in the procurement of land for agricultural land.